A model for implementation of total quality management practices on education performance in Iraq secondary schools - Kadhim, Sami Abdullah (2020)
Total Quality Management (TQM) is important in determining that an organisation can sustain in improving its competitiveness. TQM is one of the solutions for improving performance in an organisation. Education sector is still one of the greatest concerns in Iraq. The scope of this study is Iraq secondary schools. Iraq is one of the most important countries that gave special attention to education sector. However, Iraq secondary schools faces many challenges in students' learning, such as poor educational performance, lack of infrastructure for educational institutions, school facilities and lack of student satisfaction. Furthermore, most previous works have given less emphasis on Compliance (CO) and Information Technology (IT) as mediators between TQM and Education Performance (EP); this has thus been identified as a theoretical gap. The main objective of this study is to develop TQM model with Compliance (CO) and Information Technology IT) as mediators. The study applied Structural Equation Modelling (SEM) approaches to validate the proposed model. Data were collected through questionnaire, distributed to secondary school in Iraq. Data were obtain from 354 secondary schools in Iraq with 20.76% response rate. The structural model results proved that TQM has a significant impact on educational performance. This study revealed that Compliance (CO) and Information Technology (IT) were important as mediators between TQM and educational performance. This is a theoretical and managerial finding that adds to the existing literature on quality management since very few studies have conducted combining Compliance (CO) and Information Technology (IT) as mediators in the proposed TQM model. The results of this study are expected to be useful, and hope to be a guide for secondary school principals to improve educational performance through TQM applications.